Pembuatan Media Belajar Berupa Alat Peraga untuk Meningkatkan Minat Belajar Siswa di Sekolah Dasar Negri Sukosari dan Madrasah Ibtidaiyah Sukosari Mantup Lamongan - Abidah, Zakiyatul; Nashihin, Nashihin; As-Shafah Q. P., Kholbu; Nisa’, Kholifatun; Farihishobah, Muhammad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
SDN Sukosari and MI Tarbiyatul Ulum which are located in Sukosari Village, Mantup District, Lamongan Regency, where the majority of students who are still occupying the first grade are still weak in recognizing the letters of the alphabet and numbers. Thus, it is hoped that the creation of learning media in the form of praga tools can help students recognize the letters of the alphabet and numbers, moreover they will be able to read and understand more about subtraction and addition faster. This mentoring activity was carried out in Sukosari Village, Mantup District, Lamongan Regency, in less than one month starting on 03 August-27 August 2022. The objects targeted for the implementation of this program are formal educational institutions, namely SDN 1 Sukosari and MI Tarbiyatul Ulum sukosari. making learning media praga tools in the form of pictures that are used to help students to more easily understand the learning delivered. The implementation of this program is carried out on students in grades one and two for the MI Tarbiyatul Ulum institution, and grades one and six for SDN 1 Sukosari